El deterioro del Baluarte de San Pedro, un estudio de caso - Reyes, J.; Silva, I.; Pérez, T.; Corvo, F.; MartínezW.; Alonso-Guzmán, E. M.; Quintana, P. (Revista ALCONPAT, 2012)
The downtown of San Francisco de Campeche, México, has several civilian and militarian ancient buildings dating from the Hispanic colonization. These buildings are exposed to environmental agents such as high relative humidity and temperature, sun radiation, wind erosion, biologic action and anthropogenic products, which produce their deterioration. The objective of this paper is to present and discuss the diagnosis of deterioration of the San Pedro bastion as well as the possible origin of black crusts observed over the walls. Visual inspection and X Ray Diffraction analysis detected gypsum at south and southwest walls, which is indicative of the action of combustion products of vehicles circulation over neighboring avenues. Moreover, it was observed abundant microbial colonization, which activity is related to the presence of calcium oxalates that are evidence of a bio-deterioration process. Keywords: deterioration; historic buildings; San Francisco de Campeche; Bastion of San Pedro; biodeterioration